Pengembangan Perangkat Pembelajaran Fisika Berbasis Multimedia Pada Materi Impuls Dan Momentum - Daniel Rutdjiono; Nuris Dwi Setiawan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
This study aims to design and develop an effective learning media and become a media to assist in studying Physics in depth at SMK Mataram Semarang, especially in the Impulse and Momentum material. Physics becomes a boring subject for students, because many students think that Physics is a lesson that is difficult to understand, less interesting and feels monotonous. This has an impact on decreasing students' interest and value in studying Physics.The research was conducted using the Research and Development (R&D) method with six stages, namely Research and Information Collecting (Research and Information Gathering), Planning (planning), Develop Premliminary Form of Product (Product Design Making), Premliminary Field Testing (Product Design Validation) , Main Product Revision (Design Revision), Main Field Testing (Product Testing of Products in the Field by Prospective Users). Determination of the feasibility level of multimedia-based learning media based on design validation by experts and product trials to students using a research instrument in the form of a questionnaire. The development of multimedia-based learning devices can develop devices that have been used so far, from conventional devices to become more interesting learning media. The application of multimedia-based learning media can help support the teaching and learning process to make it easier to explain or deliver material to students. In addition, it can help students to understand more deeply so that students' scores can be increased more than without using learning media.